THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION ORGANIZATION CITIZENSHIP BEHAVIOR OF MAYBANK FINANCE EMPLOYEES WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - RM Faris Dencik (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
OCB behavior is shown by employees as a whole will build the continuity and success of the company. Transformational leadership, job satisfaction and organizational commitment are variables that create the emergence of OCB behavior. The formulation of the problem in this research is to find out whether there is a direct influence of transformational leadership and job satisfaction on organizational commitment and OCB, is there an influence of transformational leadership and job satisfaction on OCB through organizational commitment as an intervening variable. The population in this study were employees of the Maybank Finance company, a sample of 85 respondents. The research results show a significant influence between t-statistical variables in the direct influence interaction, namely (1) Transformational leadership on organizational commitment (2.547), (2) Job satisfaction on organizational commitment (2.302), (3) Transformational leadership on OCB (2,296), (4) Job satisfaction towards OCB (2,345), (5) Organizational Commitment towards OCB (3,977). Meanwhile, the results of calculating the indirect effect also show that Organizational Commitment is a mediating variable between Transformational Leadership (2.373) and Job Satisfaction (2.015).